Da formulação da política curricular para a educação infantil do município de São Paulo à sua implementação: princípios, concepções e sua tradução - Fratelli, Minéa Paschoaleto (2022)
This research focuses on the processes of education formulation and implementation of the Common Education Policy (BNCC) having as research universe the Municipal Department of Education of Education of São Paulo, specifically, the Curriculum of the City of Early Childhood Education. The research problem results from the perception that there is a gap between the teacher and the formulation of policy, and his research question resulting from the problem: what are the curricular principles and conceptions of policy and early childhood education in the city of São Paulo and how are they translated into practice by educational agents? Our objective is these principles and understandings that materialize in the classroom, considering that organizations have been influenced by multilateral organizations that are at the service of a new world educational order of a neoliberal character. From an epistemological point of view, we adopted the critical theories of the curriculum as a theoretical foundation. Methodologically, we adopted a qualitative and quantitative approach using data and interviews as well as instruments to approach the analysis cycle, such as the analysis of the analysis cycle, along the French line, as an analysis technique. As fundamental categories were Educational Policy Formulation, Curriculum, Curriculum Translation and Teaching Practice. Documentary analysis and research instruments allow us to verify that there is, in fact, a set of international and national influences that impact the production of the educational policy text, especially in peripheral developing countries. However, the processes of interpretation and translation, presented by the educators, allowed, through processes of resistance and (re)creation, emancipatory practices that consider the existing diversity in the municipal network.